2012
DOI: 10.1177/230949901202000327
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Atlanto-Occipital Dislocation: A Case Report

Abstract: We report a 30-year-old man with atlanto-occipital dislocation after a traffic accident. Diagnosis was based on radiography, computed tomography, and magnetic resonance imaging. Owing to the critical conditions that did not fulfil advanced trauma and life support protocols, surgical treatment was deferred, and the patient died 10 hours later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Traumatic AOD results from high-energy impact to the craniovertebral junction, usually causing ligamentous injury with rupture of the tectorial membrane and alar ligaments [7,13,14,[17][18][19][20][21]. Our review confirmed that MVAs are the most commonly reported cause of AOD.…”
Section: Discussionsupporting
confidence: 69%
“…Traumatic AOD results from high-energy impact to the craniovertebral junction, usually causing ligamentous injury with rupture of the tectorial membrane and alar ligaments [7,13,14,[17][18][19][20][21]. Our review confirmed that MVAs are the most commonly reported cause of AOD.…”
Section: Discussionsupporting
confidence: 69%
“…Neurologic deficits from AOD can range from normal neurological exam which is found in up to 20% of patients, to instant fatality ( 2 , 3 ). Initial screening lateral cervical radiograph is an acceptable first-line test, although more frequently cervical spine CT is the first imaging test done of the cervical spine.…”
Section: Discussionmentioning
confidence: 99%